2005
DOI: 10.1038/sj.leu.2403732
|View full text |Cite
|
Sign up to set email alerts
|

Significance of chemokine receptor expression in aggressive NK cell leukemia

Abstract: Natural killer (NK) cell-type lymphoproliferative diseases of granular lymphocytes can be subdivided into aggressive NK cell leukemia (ANKL) and chronic NK cell lymphocytosis (CNKL). One reason for the poor outcome in ANKL is leukemic infiltration into multiple organs. The mechanisms of cell trafficking associated with the chemokine system have been investigated in NK cells. To clarify the mechanism of systemic migration of leukemic NK cells, we enrolled nine ANKL and six CNKL cases, and analyzed the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Finally, the cells are removed from the top of the membrane, and the migratory cells are stained and quantified. The migration distance through the filter was measured in micrometers using the leading-front technique as previously described (40). Our data demonstrate that p12 expression increased the ability of cells to migrate through filters (Fig.…”
Section: Generation Of Htlv-1 P12mentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, the cells are removed from the top of the membrane, and the migratory cells are stained and quantified. The migration distance through the filter was measured in micrometers using the leading-front technique as previously described (40). Our data demonstrate that p12 expression increased the ability of cells to migrate through filters (Fig.…”
Section: Generation Of Htlv-1 P12mentioning
confidence: 89%
“…Cell migration was assessed essentially as described previously (40,71). Cells were incubated in the absence of IL-2 for 4 h and then added to the top of a 5-m polycarbonate membrane (Neuro Probe, Inc.) soaked with 10 g/ml ICAM (R&D Systems) in a chemotaxis chamber containing various amounts of IL-2 in the lower chamber.…”
Section: Methodsmentioning
confidence: 99%
“…CXCR4 expressed by tumor cells may also interact with CXCL12 to facilitate tumor growth and escape from oxygen starvation-induced apoptosis (3)(4)(5)(6)(7). In several malignancies, tumor cell expression of chemokine receptors is associated with more aggressive disease and poorer prognosis (8)(9)(10)(11). Similar to CXCR4, CXCR3 has now been identified in a variety of malignant cells, including melanoma, breast and prostate carcinomas, neuroblastoma, and a subset of B cell lymphomas (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that ANKL cells are positive for CXCR1 and CCR5, whose major ligands are CXCL8 (interleukin-8, IL-8) and CCL3 (MIP-1alpha, macrophage inflammatory protein type 1 alpha), CCL4 (MIP-1beta) and CCL5 (RANTES, regulated on activation, normal T cell expressed and secreted), respectively [128]. In addition, the serum level of IL-8, MIP-1alpha and MIP-1beta, are significantly elevated in ANKL patients and ANKL cells are positive for IL-8, MIP-1alpha, MIP-1beta and RANTES [129].…”
Section: Cell Motility and Tissue Invasionmentioning
confidence: 99%
“…These include genes codifying for matrix metallopeptidases and their inhibitors, cathepsins and chemokines, among others [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129].…”
Section: Cell Motility and Tissue Invasionmentioning
confidence: 99%